2011
DOI: 10.1007/s11064-011-0626-8
|View full text |Cite
|
Sign up to set email alerts
|

Pericyte-derived Glial Cell Line-derived Neurotrophic Factor Increase the Expression of Claudin-5 in the Blood–brain Barrier and the Blood-nerve Barrier

Abstract: The destruction of blood-brain barrier (BBB) and blood-nerve barrier (BNB) has been considered to be a key step in the disease process of a number of neurological disorders including cerebral ischemia, Alzheimer's disease, multiple sclerosis, and diabetic neuropathy. Although glial cell line-derived neurotrophic factor (GDNF) and brain-derived neurotrophic factor (BDNF) facilitate neuronal or axonal regeneration in the brain or peripheral nerves, their action in the BBB and BNB remains unclear. The purpose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
102
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(113 citation statements)
references
References 46 publications
4
102
2
Order By: Relevance
“…97 Shimizu et al demonstrated that the GDNF, secreted from the brain and peripheral nerve pericytes, is one of the key molecules responsible for the up-regulation of claudin-5 expression and the permeability in the BBB. 98 Furthermore, pericytes are able to internalize the amyloid-b peptides, which accumulate in brain of Alzheimer's disease patients. 97 With amyloid deposits detected within degenerating pericytes in the brains of patients with Alzheimer's disease, it seems that pericyte dysfunction may also play a role in cerebral hypoperfusion and impaired amyloid b-peptide clearance in Alzheimer's disease.…”
Section: Astrocytesmentioning
confidence: 99%
“…97 Shimizu et al demonstrated that the GDNF, secreted from the brain and peripheral nerve pericytes, is one of the key molecules responsible for the up-regulation of claudin-5 expression and the permeability in the BBB. 98 Furthermore, pericytes are able to internalize the amyloid-b peptides, which accumulate in brain of Alzheimer's disease patients. 97 With amyloid deposits detected within degenerating pericytes in the brains of patients with Alzheimer's disease, it seems that pericyte dysfunction may also play a role in cerebral hypoperfusion and impaired amyloid b-peptide clearance in Alzheimer's disease.…”
Section: Astrocytesmentioning
confidence: 99%
“…Although it has been demonstrated that RET/GFR␣ signaling is dispensable for thymic T cell development (3), application of GDNF led to a decrease in TNF-␣ secretion in monocytes (59). Furthermore, GDNF directly influences the blood-brain barrier by upregulation of the tight junction protein claudin 5, which leads to barrier-stabilizing effects (50,63).…”
Section: Gdnf Directly Promotes Barrier Maturation and Proliferation mentioning
confidence: 99%
“…Pericytes are one of the key players in angiogenesis and blood-brain-barrier integrity (Armulik et al, 2010). They also contribute to local homeostasis, secrete growth factors (Shimizu et al, 2012) and inflammatory molecules (Kovac et al, 2011) and are multipotent cells (Dore-Duffy, 2008;Ozen et al, 2012;Ozen et al, 2014;Paul et al, 2012)). Importantly, cerebral pericytes express platelet-derived growth factor (PDGF) receptor β (PDGFRβ) (Winkler et al, 2010), and are recruited by PDGF-BB-secreting endothelial cells to stabilise newly formed blood vessels (Armulik et al, 2005).…”
Section: Introductionmentioning
confidence: 99%